Sensory impairment and cognitive decline among older adults: An analysis of mediation and moderation effects of loneliness - Ge, Shaoqing; Pan, Wei; Wu, Bei; Plassman, Brenda L.; Dong, XinQi; McConnell, Eleanor S. (Frontiers in Neuroscience, 2023)
Background Multiple studies have reported that hearing and vision impairment are linked to cognitive decline. Yet little is known about factors that may influence the association between sensory impairment and cognitive decline. This study examined if loneliness mediates or moderates the impact of sensory impairment on cognitive decline as individuals age. Methods This was a longitudinal study using data from the Health and Retirement Study (HRS) and The Aging, Demographics, and Memory Study (ADAMS) (N = 243). We used one timepoint of hearing and vision (ADAMS 2006-2008), one timepoint of loneliness (HRS 2006-2008), and five waves of cognition (HRS 2006–2014). Hearing impairment was defined by an inability to hear pure-tone stimuli of 25dB at frequencies between 0.5 – 4.0kHz in either ear. Visual impairment was defined as having corrected binocular vision worse than 20/40. Longitudinal parallel-process (LPP) analysis was conducted at a significance level of α = .05 (one-tailed). Results Loneliness moderated but did not mediate the association between visual impairment and the rate of cognitive decline (standardized β = -.108, p < .05). No moderation or mediation effect of loneliness was found for the association between hearing impairment and cognitive decline. Both vision and hearing impairment were significantly associated with increased severity of loneliness. Conclusions Visual impairment combined with an elevated level of loneliness may produce a more synergistic, deleterious impact on older adults’ cognitive function than visual impairment alone. This study highlights the importance of promoting a healthy social and psychological status for older adults with sensory impairment.